Improving reporting of meta-ethnography: the eMERGe reporting guidance - France, Emma F. (BMC Med Res Methodol, 2019)
AIMS: The aim of this study was to provide guidance to improve the completeness and clarity of meta-ethnography reporting. BACKGROUND: Evidence-based policy and practice require robust evidence syntheses which can further understanding of people’s experiences and associated social processes. Meta-ethnography is a rigorous seven-phase qualitative evidence synthesis methodology, developed by Noblit and Hare. Meta-ethnography is used widely in health research, but reporting is often poor quality and this discourages trust in and use of its findings. Meta-ethnography reporting guidance is needed to improve reporting quality. DESIGN: The eMERGe study used a rigorous mixed-methods design and evidence-based methods to develop the novel reporting guidance and explanatory notes. METHODS: The study, conducted from 2015 to 2017, comprised of: (1) a methodological systematic review of guidance for meta-ethnography conduct and reporting; (2) a review and audit of published meta-ethnographies to identify good practice principles; (3) international, multidisciplinary consensus-building processes to agree guidance content; (4) innovative development of the guidance and explanatory notes. FINDINGS: Recommendations and good practice for all seven phases of meta-ethnography conduct and reporting were newly identified leading to 19 reporting criteria and accompanying detailed guidance. CONCLUSION: The bespoke eMERGe Reporting Guidance, which incorporates new methodological developments and advances the methodology, can help researchers to report the important aspects of meta-ethnography. Use of the guidance should raise reporting quality. Better reporting could make assessments of confidence in the findings more robust and increase use of meta-ethnography outputs to improve practice, policy, and service user outcomes in health and other fields. This is the first tailored reporting guideline for meta-ethnography. This article is being simultaneously published in the following journals: Journal of Advanced Nursing, Psycho-oncology, Review of Education, and BMC Medical Research Methodology. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12874-018-0600-0) contains supplementary material, which is available to authorized users.